DAMPAK COVID-19 TERHADAP HARGA SAHAM GABUNGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Melly Meilani; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2021)
This study aims to determine the impact of Covid-19 on the price of joint stock listed on the Indonesia stock exchange. The population used in this study are all companies listed on the Indonesia Stock Exchange (BEI) and also listed as IDX30 index companies. Number of samples are 30 companies. The data analysis method used was the Wilcoxon Signed Ranks Test. The results of hypothesis testing using the Wilcoxon Signed Ranks Test show that the average Composite Stock Price Index before and after the announcement of the Covid-19 Pandemic shows an asymptotic significance value (2-tailed) of 0.005. This value < 0.05, which means that H0 is rejected and H1 is accepted. This means that there are differences before and after the announcement of the Covid-19 Pandemic against the Composite Stock Price Index on the IDX30 Index. Keywords : Covid-19 Pandemic Events, Composite Stock Price Index